Corrigendum to “Spectra universally realizable by doubly stochastic matrices” - Collao Macarena; Salas Mario; Soto Ricardo L. (Special Matrices, 2023)
We correct an error in the statement and the proof of Theorem 2.1 and Corollary 2.1 in our previous study [Spec. Matrices 6 (2018), 301–309], Section 2: On nonnegative matrices similar to positive matrices.